Book Reviews - Julie Nichols; Brad E. Lucas; Maureen Hall; Gae Lyn Henderson (Journal of the Assembly for Expanded Perspectives on Learning, 2017)
Julie Nichols - Threshold Concepts. Brad E. Lucas, et al. - Adler-Kassner, Linda, and Elizabeth Wardle, eds. Naming What We Know: Threshold Concepts of Writing Studies. Logan: Utah State University Press, 2015. Maureen Hall - Waxler, Robert P. The Risk of Reading: How Literature Helps Us to Understand Ourselves and the World. New York: Bloomsbury, 2014. Gae Lyn Henderson - Goodson, Ivor, and Scherto Gill. Critical Narrative as Pedagogy. New York: Bloomsbury, 2014.